Case report: Durable response to ruxolitinib in a child with TREX1-related disorder - Bin Khathlan, Yasir; Almutairi, Sajdi; Albadr, Fahad B.; Alangari, Abdullah A.; Alsultan, Abdulrahman (Frontiers in Pediatrics, 2023)
Background: JAK inhibitors are useful in treating interferonopathies, presumably because they downregulate the JAK/STAT signaling. There are limited studies about the safety and effectiveness of using JAK inhibitors in children with TREX1-related disorders. Case presentation: We report an 8-year-old female who presented at five years of age with features suggestive of hemophagocytic lymphohistiocytosis (HLH)-like disorder. The infectious disease workup was negative. Neurological assessment was normal. A brain CT scan was performed because of headache. It showed a faint subcortical calcification at right frontal lobe and almost symmetrical calcification within the basal ganglia. Brain MRI showed bilateral symmetrical globus pallidus, high T1 signal intensities, and a few scattered nonspecific FLAIR hyperintensities in subcortical and deep white matter. IVIG as an immune modulating agent was administered initially which led to the resolution of fever, improvement of blood count parameters, inflammatory markers, and normalization of liver enzymes. The child remained afebrile with no significant events for several months, then had disease flare up. The patient was started on pulse methylprednisolone 30 mg/kg for three days, then continued on 2 mg/kg. Whole exome sequencing revealed a novel heterozygous missense TREX1 mutation NM_016381.3:c.223G>A p.(Glu75Lys). The child was started on ruxolitinib, 5 mg orally twice daily. The child has prolonged, durable remission after initiating ruxolitinib with no adverse effects. Steroids were tapered off and the patient is no longer on IVIG. The patient is still on ruxolitinib for more than two years. Conclusion: This case highlights the potential role of ruxolitinib in the treatment of TREX1-related disorders. A longer follow-up period is required to evaluate the long-term outcome.